2020
DOI: 10.1038/s41598-020-76748-1
|View full text |Cite
|
Sign up to set email alerts
|

Identifying potential biomarkers related to pre-term delivery by proteomic analysis of amniotic fluid

Abstract: We sought to identify biomarkers in the amniotic fluid (AF) and specific signaling pathways related to spontaneous preterm delivery (SPTD, < 34 weeks) in women with preterm labor (PTL) without intra-uterine infection/inflammation (IUI). This was a retrospective cohort study of a total of 139 PTL women with singleton gestation (24 + 0 to 32 + 6 weeks) who underwent amniocentesis and who displayed no evidence of IUI. A nested case–control was conducted using pooled AF samples (n = 20) analyzed via label-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 55 publications
2
21
1
Order By: Relevance
“…In the present study, we have demonstrated that LXR/RXR activation plays a significant role in the pathogenesis of PTL and SPTB without IAI. This is, in principle, in agreement with previous proteomic studies conducted using maternal blood or AF samples that demonstrated the role of diabetes/lipid metabolisms in the development of idiopathic SPTB [ 28 , 42 , 61 ]. Indeed, these observations are not unexpected because human and primate studies have corroborated that decreased maternal glucose levels and maternal dyslipidemia are directly linked to an increased risk of SPTB [ 63 , 64 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, we have demonstrated that LXR/RXR activation plays a significant role in the pathogenesis of PTL and SPTB without IAI. This is, in principle, in agreement with previous proteomic studies conducted using maternal blood or AF samples that demonstrated the role of diabetes/lipid metabolisms in the development of idiopathic SPTB [ 28 , 42 , 61 ]. Indeed, these observations are not unexpected because human and primate studies have corroborated that decreased maternal glucose levels and maternal dyslipidemia are directly linked to an increased risk of SPTB [ 63 , 64 ].…”
Section: Discussionsupporting
confidence: 91%
“…We could not find any data related to our findings in published literature. Nonetheless, we propose that the relationship between lower S100A9 levels in the plasma and SPTB without IAI may be explained by the findings reported by Averill et al [ 40 ], given that immune/inflammatory-related pathways may still be important common pathways that lead to term and preterm parturition, despite excluding the cases of IAI [ 41 , 42 ]. Averill et al showed that among three different myeloid cell populations (dendritic cells, macrophages, and neutrophils), S100A9-deficient dendritic cells exhibit an exacerbated release of cytokines (anti-inflammatory), whereas S100A9-deficient neutrophils show a reduced secretion of cytokines (pro-inflammatory) [ 40 ].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, other molecules and pathways have been monitored in relation to IAI, preterm labor and preterm birth in order to find specific and reliable biomarkers to evaluate the risk of pregnancy complications. For instance, a study by Hong et al (178) identified several proteins and pathways with altered protein levels in the hAF, such as vascular endothelial growth factor receptor 1 and Fc fragment of IgG binding protein, and pathways of glycolysis, gluconeogenesis, and iron homeostasis (178). In line with this, glucose concentration in the hAF was lower in case of IAI, while hepcidina regulator of iron releasewas increased (203,204).…”
Section: The Potential Feasibility and Problems Of The Existing Iai Biomarkersmentioning
confidence: 90%
“…Human neutrophil (or alpha) defensins (HNPs)1-3, lysozyme and lactoferrin were also found in the hAF in women with non-complicated pregnancies ( 170 , 182 ). Moreover, HNP1-3, calgranulin/calprotectin, bactericidal permeability-increasing protein, lactoferrin, lipocalin 2 and cathelicidin family members are increased in the hAF of IAI or preterm labor ( 100 , 101 , 150 , 152 , 166 , 168 , 169 , 171 , 177 , 178 , 183 , 179 , 180 ) Overall, the presence and activation of numerous variable AMPs in normal pregnancy and in IAI imply an important role of AMPs in prevention and resolution of infections.…”
Section: Innate Immune System Defense Against Pathogens In the Haf And Hammentioning
confidence: 99%